Пирожное с хреном - Lidin, Konstantin (проект байкал, 2007)
Huge urban agglomerations of the world become bigger and more numerous. In 2000 there were 16 giant cities with population more than 10 million people, and by 2015 their number will have grown up to 21. However the biggest share of the global urban population increase falls on relatively small places with population from 500,000 to 5 million people. Within 2000-2015 the tendencies will be similar. Global urbanization engrosses more and more countries and regions. Mankind keeps on growing irregularly – population increase is concentrated in cities. It is obvious why human masses gather in big cities: the life in such cities is more comfortable than in rural area. Of course, poverty and despondent imbecility of rural life looks less attractive than city apartment and rapid rhythm of life in a megapolis. Finally, it is desire for better comfort – accommodation, activity and reasonableness of living – that leads immigrants to the city. In some cases the number of immigrants is so big that city population increases several times within the life of one generation. In other words, there are more newcomers that the natives of the city. In this case the tendency towards «discomfortization » embraces the whole megapolis. In the urban development science such effect is called «degradation of urban environment ». Tokyo and London of the seventies-nineties of the last century can be examples of this. Vsevolod Ovchinnikov describes «the Oriental capital»: «Tokyo is a hypertrophied embodiment of the problems peculiar to megapolises in general and to an overpeopled insular country in particular. This paradoxical combination of tightness and chaos, density and dispersion… Tokyo citizens have a joke that even their dogs have to wag their tails not from side to side, but upward and downward». In addition to the problems of pure air and water, transport and noise there is a tremendous ugliness of urban development. Plenty of individual beautiful buildings do not make the general impression better: «Try to find a point for panoramic picture for everybody to say: what a beautiful city! Even the perfection of Japanese photographic apparatuses cannot be helpful. You need not a tripod but at least a helicopter… Hundreds of monumental buildings are lost like a mosaic fallen to pieces, which could compose a wonderful picture if architects worked in collaboration with city planners». It can hardly be said that some definite people deliberately and purposefully came to a decision to make the city uncomfortable for living. The situation looks like an unintentional reflective reaction of a primitive living organism – it is a rejection of irritant factor. The city, like a living but unreasonable being, tries to push out its «excess» people. If authorities do not take upon themselves the functions of reason, that is planning and management, the urban environment degrades very quickly. Instead of expected welfare citizens get a pastry filled with horseradish – life dressed with many problems and oppressive discomfort.